2004
DOI: 10.1086/380899
|View full text |Cite
|
Sign up to set email alerts
|

Old and Young X‐Ray Point Source Populations in Nearby Galaxies

Abstract: We have analyzed Chandra ACIS observations of 32 nearby spiral and elliptical galaxies and present the results of 1441 X-ray point sources that were detected in these galaxies. The total point-source X-ray (0.3−8.0 keV) luminosity L XP is well correlated with the B-band, K-band, and FIR+UV luminosities of spiral host galaxies, and is well correlated with the B-band and K-band luminosities for elliptical galaxies. This suggests an intimate connection between L XP and both the old and young stellar populations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
300
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(341 citation statements)
references
References 54 publications
38
300
3
Order By: Relevance
“…Fitting the CLF of the bulge of M 31, Shirey et al (2001) find a slope of 1.77 ± 0.35 for 37.4 ≤ log L X erg s −1 < 38.1, flattening to α = 0.43 for log L X erg s −1 < 37.4. According to the surveys of Colbert et al (2004) and Kilgard et al (2002) galaxies with ongoing or recent star formation show flatter CLFs than elliptical galaxies consisting of old populations. Comparing the slope of the bulge CLF from Shirey et al (2001) with those of the disc from this work (see Table 6) show that the CLF of the disc is flatter than that of the core.…”
Section: Luminosity Functionsmentioning
confidence: 99%
“…Fitting the CLF of the bulge of M 31, Shirey et al (2001) find a slope of 1.77 ± 0.35 for 37.4 ≤ log L X erg s −1 < 38.1, flattening to α = 0.43 for log L X erg s −1 < 37.4. According to the surveys of Colbert et al (2004) and Kilgard et al (2002) galaxies with ongoing or recent star formation show flatter CLFs than elliptical galaxies consisting of old populations. Comparing the slope of the bulge CLF from Shirey et al (2001) with those of the disc from this work (see Table 6) show that the CLF of the disc is flatter than that of the core.…”
Section: Luminosity Functionsmentioning
confidence: 99%
“…The reason for this is that the detection of HMXBs in M 31 is difficult. Colbert et al (2004) showed that the hardness ratio method is very inefficient in selecting HMXBs in spiral galaxies. The selection process is complicated by the fact, that the spectral properties of BH HMXBs, which have power-law spectra with indices of ∼1-∼2 are similar to LMXBs and AGN.…”
Section: Detection Of High Mass X-ray Binariesmentioning
confidence: 99%
“…Therefore the region in the HR diagrams where BH HMXB are located is contaminated by other hard sources (LMXBs, AGN, and Crab-like SNRs). For the NS HMXBs, which have power-law indices of ∼1, and thus should be easier to select, the uncertainties in the hardness ratios lead at best to an overlap -in the worst case to a fusion -with the area occupied by other hard sources (Colbert et al 2004). …”
Section: Detection Of High Mass X-ray Binariesmentioning
confidence: 99%
“…Previous studies of the X-ray emission produced by starformation have been focused on nearby starbursts (e.g., Ptak et al 1999;Jiménez-Bailón et al 2003;Ranalli et al 2003;Grimm et al 2003;Persic et al 2004;Colbert et al 2004) or ULIRGs (e.g., Rieke 1988;Perez-Olea & Colina 1996;Ptak et al 2003;Franceschini et al 2003;Teng et al 2005;Teng & Veilleux 2010).…”
Section: Introductionmentioning
confidence: 99%